2015
DOI: 10.1186/2044-7248-4-17
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a kokumi peptide, γ-glutamyl-valyl-glycine, on the sensory characteristics of chicken consommé

Abstract: Background: Recent studies have demonstrated that kokumi substances such as glutathione are perceived through the calcium-sensing receptor (CaSR). Screening by a CaSR assay and sensory evaluation have shown that γ-glutamyl-valyl-glycine (γ-Glu-Val-Gly) is a potent kokumi peptide. In the present study, the sensory characteristics of chicken consommé with added γ-Glu-Val-Gly were investigated using descriptive analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 18 publications
(30 reference statements)
2
21
0
Order By: Relevance
“…It was found that 0.01% 35 in standard solution produced the sensory activity equivalent to 0.128% 36; therefore, we estimated that the sensory activity of kokumi peptide 35 is 12.8-fold greater than that of 36. 7,[32][33][34] Similarly, the sensory activity of Nva-containing tripeptide 48 and dipeptide 18 were approximately 200-and 100-fold greater than that of 36, i.e., 20-and 10-fold greater than that of 35, respectively. The taste recognition threshold concentration of 48 (0.028 ppm) and 18 (0.077 ppm) were significantly lower than that of 35 (0.47 ppm) (see Experimental).…”
Section: Resultsmentioning
confidence: 99%
“…It was found that 0.01% 35 in standard solution produced the sensory activity equivalent to 0.128% 36; therefore, we estimated that the sensory activity of kokumi peptide 35 is 12.8-fold greater than that of 36. 7,[32][33][34] Similarly, the sensory activity of Nva-containing tripeptide 48 and dipeptide 18 were approximately 200-and 100-fold greater than that of 36, i.e., 20-and 10-fold greater than that of 35, respectively. The taste recognition threshold concentration of 48 (0.028 ppm) and 18 (0.077 ppm) were significantly lower than that of 35 (0.47 ppm) (see Experimental).…”
Section: Resultsmentioning
confidence: 99%
“…Panelists defined each term and set reference standards for understanding the terms during a consensus training session (Lawless & Civille, ). Sensory terms were developed by referring to previous studies (Kohno et al, ; Lyon, ; Miyaki et al, ; Tian et al, ), and the definition and reference standards of the terms were chosen through discussion similar to previous studies (Miyaki et al, ; Pujchakarn, Suwonsichon, & Suwonsichon, ; Talavera & Chambers, ).…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, there have been several research related to sensory characteristics of chicken broth. Miyaki, Kawasaki, Kuroda, Miyamura, and Kouda () studied effect of kokumi peptide by making chicken consommé. They developed sensory attributes of chicken consommé, defined and set reference standards of each sensory term.…”
Section: Introductionmentioning
confidence: 99%
“…Kokumi compounds have only a minimal flavour in water, but if added to some foods, they can substantially enhance the thickness, continuity, and mouthfulness of the food to which they have been added (Miyaki et al, 2015). Recently, it was reported that kokumi substances such as GSH are perceived through the calcium-sensing receptor (CaSR) in humans (Ohsu et al, 2010).…”
Section: Kokumimentioning
confidence: 98%